Linear algebra and its applications - Strang, Gilbert (Harcourt, 1988)
Contents: Matrices and gaussian elimination; The geometry of linear equations; An example of gaussian elimination; Matrix notation and matrix multiplication; Triangular factors and row exchanges; Inverses and transposes...